2020
DOI: 10.33545/gynae.2020.v4.i3c.596
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ectopic pregnancy in women: A case control study

Abstract: Introduction: Ectopic pregnancy can mimic practically each and every gynaecological disorder as well as many surgical catastrophes. It has always challenged ingenuity of the obstetricians and gynaecologists by its bizarre clinical picture. If it is not diagnosed attended in time, it may lead to maternal morbidity and mortality. Methodology: This study was conducted on 440 patients at Government Medical College, Srinagar between Jan 2018 and March 2020. All study participants consented in writing. The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The cohort study by Saetta et al (2020) concluded that endometriosis is not a risk factor for ectopic pregnancy, in line with the results of a study by Gaskins et al (2018). The opposite result was presented in the study by Muzaffar et al (2020), Hwang et al (2016) and Farland et al (2019) which states that endometriosis increases the risk of ectopic pregnancy.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…The cohort study by Saetta et al (2020) concluded that endometriosis is not a risk factor for ectopic pregnancy, in line with the results of a study by Gaskins et al (2018). The opposite result was presented in the study by Muzaffar et al (2020), Hwang et al (2016) and Farland et al (2019) which states that endometriosis increases the risk of ectopic pregnancy.…”
supporting
confidence: 58%
“…Assouni-Mindjah et al (2018) conducted a case-control study on 264 women and found that the IUD did not significantly increase the risk of ectopic pregnancy. While Muzaffar et al (2020) in their study found that IUD use increases the risk of ectopic pregnancy. Meta-analysis by Mol et al (1995) and Xiong et al (1995) concluded that IUD use generally reduces the incidence of ectopic pregnancy when not pregnant, but that when a woman with an in-situ IUD becomes pregnant, the risk of ectopic implantation increases.…”
mentioning
confidence: 95%